Interoperability Inspection Method in Electronic Government Based on e-PING Architecture - Silva, Breno Augusto Ferreira Gonçalves; Maciel, Cristiano; Silva Junior, Deógenes Pereira da (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Government systems and websites facilitate various processes and services provided to the population, but many of them do not fulfill all the proposed functions or fail to meet the population’s needs. This research presents a proposal of an inspection method to evaluate governmentalwebsites, called electronic government, in order to identify problems related to the interoperability of systems, which means the ability of two systems to communicate without external effort being necessary. For the method elaboration, concepts of interoperability, inspection methods and checklist were revised. Also, we performed an analysis of the e-PING interoperability standard, created for the Brazilian electronic government, in order to develop criteria and guidelines for the method. The purpose of this paper is present the method’s creation and its viability evaluation. The evaluation, based in an use example, had the intention of producing a method with consistent and verisimilar criteria. As principal results, in general the method has a short time execution time, with durations from 50 to 80 minutes, the developed method received some adjustments, such as new fields in the checklist, and we perceived homogeneity in the degree of method’s understanding.